2003
DOI: 10.1021/jp030768g
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Hg2+ Recognition by 1,3-Diphenyl-Thiourea

Abstract: We have studied the electronic and structural properties responsible for the molecular recognition that the 1,3-diphenyl-thiourea ionophore (L) experiences by the Hg2+ cation. The theoretical data was obtained for the bare L and for the [L−HgOH]+ and [L−Hg−L]2+ coordination compounds involved in the reaction mechanism in reported sensors. Calculations were performed with the Gaussian-98 program at the B3LYP/6-31G** level. A LANL2DZ pseudopotential was used for Hg. The calculated electrostatic potential of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 26 publications
2
21
0
3
Order By: Relevance
“…Theoretical study of the Hg 2+ recognition by 1,3-diphenylthiourea has been reported [2]. The mechanism of enantioselective Michael addition of acetylacetone to a nitroolefin catalyzed by a thiourea based chiral bifunctional organocatalyst is investigated using density functional theory calculations [3].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical study of the Hg 2+ recognition by 1,3-diphenylthiourea has been reported [2]. The mechanism of enantioselective Michael addition of acetylacetone to a nitroolefin catalyzed by a thiourea based chiral bifunctional organocatalyst is investigated using density functional theory calculations [3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their physical and chemical properties are modified by the substituents on nitrogen. Now, the chemistry of substituted thiourea derivatives has attracted increasing attention because of their potential use as reagents for the separation or recognition of metal ions [4,5] and in biological applications [6Ϫ8]. There have been many studies on N-alkyl or aryl and N,NЈ-dialkyl or diaryl substituted thioureas and related ligands coordinated to a series of metals [9Ϫ14].…”
Section: Introductionmentioning
confidence: 99%
“…The calculations were carried out using the Gaussian 09 suite of programs [17]. Previous electronic properties study on the other thiourea derivative molecules was proved reliable using B3LYP [18]. Thus, the single point calculations were performed at B3LYP level of theory with the DEF2-TZVP as the basis set.…”
Section: ■ Computational Methodsmentioning
confidence: 99%